A preservação documental no Arquivo Histórico de Porto Alegre sob a ótica do gerenciamento de riscos - Souto, Maria Lúcia Ricardo (2016)
Damage to archival collections jeopardize access to information, one of the reasons for its existence. These damages vary in the degree of degradation, from the most inconspicuous but silently lead to loss of support, even the most obvious caused by mishandling and pest infestation. This loss can happen abruptly through accidents and disasters, causing irreversible damage to the documents. Given this situation, seeking to know how to preserve and guarantee the physical security of the documentary front equity to a number of factors that lead to their destruction, the main objective of this thesis was to develop a Risk Management Plan for document preservation in Port Historical Archives Alegre Moyses Vellinho (AHPAMV). To fabricate the plan and establish more efficient priority and preventive actions to ensure the preservation of the documentary collection of the institution used the Risk Management methodology to identify and analyze the risks in AHPAMV. From the application of the methodology and analysis of the results, it was possible to build the product of this work has resulted in a publication entitled "Plan File Risk Management Port History Alegre Moyses Vellinho", will help to ensure the acquis integrity and guide decisions for the preservation of historical documents stored there. At the end of this work it was possible to verify that the objectives have been achieved to the extent that some items proposed as a treatment have been implemented since the AHPAMV work team has a good understanding of the risks facing the institution and the measures needed to sanitation them. The perceived problem is that several recommendations contained in the bump up in the question funding and bureaucracy of the municipal government of Porto Alegre to meet the requests of the institution, always complex issues in the public sphere. Finally, it is expected that the preparation of this work will serve as a subsidy for the establishment of an institutional preservation policy, which further qualify the service performed by this memory entity.